The Influence Of Financial Technology, Herding Behavior, And Risk Tolerance On The Investment Decisions Of Generation Z In Palu City - Lesmana Adelyanto Sampe; Fatlina Zainuddin; Muhammad Yunus Kasim; Rizkiani Iskandar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of financial technology, herding behavior, and risk tolerance on investment decisions of Generation Z in Palu City. This study used a quantitative approach by distributing questionnaires to 75 respondents who are active Generation Z investors. Data analysis was conducted using the multiple linear regression method. The results showed that financial technology has a positive and significant effect on investment decisions, which means that the higher the use of digital financial technology, the greater the tendency of Generation Z to make investment decisions efficiently and confidently. Meanwhile, herding behavior and risk tolerance did not have a significant effect on investment decisions, indicating that Generation Z in Palu City tends to make decisions based on rational and independent considerations. Simultaneously, these three variables influence investment decisions.